An Insightful Exploration: Sales and Business Development Internship at Gray Quest - Patil, Durgaprasad (ATLAS SkillTech University, 2025)
The internship report titled "An Insightful Exploration: Sales and Business Development Internship at Gray Quest" provides a comprehensive overview of my enriching experience as a Sales and Business Development Intern at Gray Quest, a leading fintech company. The report encapsulates the valuable insights and practical knowledge gained during this internship program, which was undertaken during the summer as part of my second-year MBA curriculum at Atlas Skilltech University. Throughout the internship, I actively participated in various aspects of the sales process, including strategizing target identification, prospecting, outreach, product demonstrations, and pipeline management. Under the guidance of Dr. Priya Harikumar, my esteemed faculty mentor, I navigated the dynamic world of B2C & B2B sales and harnessed the opportunity to bridge the gap between theoretical concepts and real-world applications. The report elaborates on the significance of this hands-on experience, highlighting its impact on my professional growth and aligning my academic knowledge with the demands of the modern business landscape. This executive summary aims to provide a glimpse into the detailed findings and reflections shared in the subsequent sections of the report, enabling readers to comprehend the value of this transformative internship experience at Gray Quest.
Project Report on An Insightful Exploration: Sales and Business Development Internship at Gray Quest (2023-2025) Under the Guidance of Prof. Priya Harikumar
Keywords: Sales and Business; B2C; B2B